Application of scanning laser Doppler vibrometry for delamination detection in composite structures. (December 2017) - Kudela, Pawel; Wandowski, Tomasz; Malinowski, Pawel; Ostachowicz, Wieslaw
Abstract: In this paper application of scanning laser Doppler vibrometry for delamination detection in composite structures was presented. Delamination detection was based on a guided wave propagation method. In this papers results from numerical and experimental research were presented. In the case of numerical research, the Spectral Element Method (SEM) was utilized, in which a mesh was composed of 3D spectral elements. SEM model included also a piezoelectric transducer. In the experimental research guided waves were excited using the piezoelectric transducer whereas the sensing process was conducted using scanning laser Doppler vibrometer (SLDV). Analysis of guided wave propagation and its interaction with delamination was based on a full wavefield approach. Attention was focused on interactions of guided waves with delamination manifested by A0 mode reflection, A0 mode entrapment, and S0/A0 mode conversion. Delamination was simulated by a teflon insert located between plies of composite material. Results of interaction with symmetrically and nonsymmetrical placed delamination (in respect to the composite sample thickness) were presented. Moreover, the authors investigated different size of delaminations. Damage detection was based on a new signal processing algorithm proposed by the authors. In this approach the weighted RMS was utilized selectively. It means that the summation in RMS formula was performed only for a specially selected time instances. Results for simple composite panels, panel with honeycomb core, and real stiffened composite panel from the aircraft were presented. Highlights: Full wavefield analysis of Lamb wave interaction with delaminations. New algorithm based on selective root mean square for delamination identification. Quantification of delamination size. Experimental validation with the use of laser vibrometer.